Addition of Broad Bean Hull to Wheat Flour for the Development of High-Fiber Bread: Effects on Physical and Nutritional Properties - Ni, Qianqian (Foods, 2020)
The seed coat (hull) of broad bean (Vicia faba) (BBH) is a significant secondary product of processing with a promising nutritional profile. Bean hull has a high fiber content (49%), yet it remains underexploited as an ingredient by the food industry. This study investigated the potential of this secondary product to partially replace wheat flour for the development of high-fiber breads. Bread formulations with a range of supplementation levels (0%, 11%, 21% and 31%) were developed and tested for their nutritional and physical properties. The proximate composition of breads revealed that at 31% replacement, the fiber content was 19.19 g/100 g bread, which was significantly higher (p < 0.05) than control breads (3.62 g/100 g bread). The physical (specific volume, density and color) and textural properties of breads were affected by the addition of bean hull. Specific volume and hardness of breads were significantly reduced at ≥21% replacement compared to the control, which may reduce acceptability of the product by some consumer groups. Enzyme-linked immunosorbent assay (ELISA) showed that the gluten content of breads was significantly reduced with bean hull addition (62% depletion for 31% replacement). At 11%, 21% and 31% replacement, one portion (80 g of bread) contains 6.8 g, 11.6 g and 15.3 g of dietary fiber, respectively, which contributes 23%, 38% and 51% of the recommended daily fiber intake (30 g/day). In conclusion, bean hull can be a valuable source of dietary fiber in bread formulations. The study showed BBH could be used to replace up to 21% of the wheat flour without significantly impacting on bread texture and volume.